The Rain Retreat: Early Monasticism as a Catalyst for Holistic Well-being and Mental Health (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The Rain Retreat (traditionally known as Vassa or Vassa-Vasa) represents a pivotal transition in early Buddhist history from a nomadic, wandering lifestyle to a settled, communal existence during the monsoon season. This period of "structured seclusion" served as a foundational catalyst for both the institutional complexity of Buddhism and the development of sophisticated systems for mental health and holistic well-being.